Africa: Opportunities for rangelands restoration through livestock value chains - Wane, Abdrahmane; Baker, Derek (International Livestock Research Institute, 2025)
The report Global Value Chains from Rangelands for Restoration and Livelihoods in Africa is part of the Sustainable Investments for Large-Scale Rangelands Restoration (STELARR) project, which aims to reverse rangeland degradation through sustainable livestock value chains. The project seeks to reduce poverty and ensure inclusive benefits for vulnerable populations, particularly women and youth. The study emphasizes the importance of both livestock and non-livestock products from rangelands, which are essential for food security and economic stability. Focusing on sustainable practices and enhancing the value chains of rangeland products can achieve significant economic and environmental benefits. Addressing the identified challenges through collaborative efforts and targeted investments will be the key to realizing the potential of these value chains to support livelihoods and restore degraded rangelands in Africa. The findings underscore rangelands’ critical role in the continent’s economy and the importance of sustainable management for future generations.